Tratamentos de sementes de melão e os efeitos sobre a qualidade sanitária e fisiológica - Müller, Juceli (2013)
Cucumis melo is one of the most important horticultural species representing the family Cucurbitaceae, moreover, it is the leader fruit concerning value and volume of exportation in Brazil. As in other cultures, both physiological and health quality of seeds used in the crop establishment are critical to ensure an appropriate population of plants and with high quality and productivity. Treatment of seeds is employed in order to protect them against pathogens, as well as, to accelerate and uniform their germination. Thus, this study aims to evaluate the physiological and health quality of melon seeds, cv. Gaúcho Redondo‟, treated with chemical fungicides, biocontrol agents, micronutrients and polymer. Application rates followed recommendations described by manufacturers. Evaluation of physiological traits was undertaken by means of germination, seedlings length, cold storage, germination at low temperatures, greenhouse emergence and emergence speed index tests. Health quality tests, by the other hand, were determined by Blotter test , transmission and pathogenicity of Fusarium spp. isolated from melon seeds. Treatments with micronutrients, purely or combined with polymer coating, incremented in seed germination, as well as, the emergence and the emergence speed index. Trichoderma spp. also provided a significant increase in the first count and germination. The fungicide Captan® acted efficiently on Fusarium spp. present in the seeds, though it had not been totally eradicated. This pathogen associated with melon seeds did not affect the germination process of them.